Sub-Municipal Governance in Europe
XII, 268 p.
Keywords: This book explores sub-municipal units’ (SMU) role in decision making, decentralized institutional innovation, social innovation and, in rural areas, service delivery. Focusing on fourteen European countries, the book examines the impact of political cultures, administrative traditions and local government systems on the functioning of the SMUs. An under-explored topic in the literature, this book provides a comprehensive, comparative European, thematically broad, descriptive book on sub-municipal governance. .